7.2k views
4 votes
8×4-5×(3⅕-2½)+(4-1)²​

User Jhickok
by
5.5k points

2 Answers

4 votes

Answer:

75/2

Explanation:

Simplify the following:

8×4 - 5 (3 + 1/5 - (2 + 1/2)) + (4 - 1)^2

Put 2 + 1/2 over the common denominator 2. 2 + 1/2 = (2×2)/2 + 1/2:

8×4 - 5 (3 + 1/5 - (2×2)/2 + 1/2) + (4 - 1)^2

2×2 = 4:

8×4 - 5 (3 + 1/5 - (4/2 + 1/2)) + (4 - 1)^2

4/2 + 1/2 = (4 + 1)/2:

8×4 - 5 (3 + 1/5 - (4 + 1)/2) + (4 - 1)^2

4 + 1 = 5:

8×4 - 5 (3 + 1/5 - 5/2) + (4 - 1)^2

Put 3 + 1/5 - 5/2 over the common denominator 10. 3 + 1/5 - 5/2 = (10×3)/10 + 2/10 + (5 (-5))/10:

8×4 - 5(10×3)/10 + 2/10 + (5 (-5))/10 + (4 - 1)^2

10×3 = 30:

8×4 - 5 (30/10 + 2/10 + (5 (-5))/10) + (4 - 1)^2

5 (-5) = -25:

8×4 - 5 (30/10 + 2/10 + (-25)/10) + (4 - 1)^2

30/10 + 2/10 - 25/10 = (30 + 2 - 25)/10:

8×4 - 5(30 + 2 - 25)/10 + (4 - 1)^2

30 + 2 = 32:

8×4 - 5 (32 - 25)/10 + (4 - 1)^2

| 2 | 12

| 3 | 2

- | 2 | 5

| 0 | 7:

8×4 - 5×7/10 + (4 - 1)^2

-5×7/10 = (-5×7)/10:

8×4 + (-5×7)/10 + (4 - 1)^2

The gcd of -5 and 10 is 5, so (-5×7)/10 = ((5 (-1)) 7)/(5×2) = 5/5×(-7)/2 = (-7)/2:

8×4 + (-1×7)/2 + (4 - 1)^2

4 - 1 = 3:

8×4 - 7/2 + 3^2

8×4 = 32:

32 - 7/2 + 3^2

3^2 = 9:

32 - 7/2 + 9

Put 32 - 7/2 + 9 over the common denominator 2. 32 - 7/2 + 9 = (2×32)/2 - 7/2 + (2×9)/2:

(2×32)/2 - 7/2 + (2×9)/2

2×32 = 64:

64/2 - 7/2 + (2×9)/2

2×9 = 18:

64/2 - 7/2 + 18/2

64/2 - 7/2 + 18/2 = (64 - 7 + 18)/2:

(64 - 7 + 18)/2

| 1 |

| 6 | 4

+ | 1 | 8

| 8 | 2:

(82 - 7)/2

| 7 | 12

| 8 | 2

- | | 7

| 7 | 5:

Answer: 75/2

User JohnWowUs
by
5.4k points
5 votes

Answer:

101/2

Explanation:

User Tyme
by
5.1k points